2019
DOI: 10.1016/j.clnu.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Timing of PROTein INtake and clinical outcomes of adult critically ill patients on prolonged mechanical VENTilation: The PROTINVENT retrospective study

Abstract: Our data suggest that although overall low protein intake is associated with the highest mortality risk, high protein intake during the first 3-5 days of ICU stay is also associated with increased long-term mortality. Therefore, timing of high protein intake may be relevant for optimizing ICU, in-hospital and long-term mortality outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(122 citation statements)
references
References 26 publications
3
93
0
12
Order By: Relevance
“…16,17 Presumably, timing of nutrition interventions 18 might play an important role, and especially early (ࣘ3 days) high protein intake may relate to negative effects. 19 Suggestions have been made that early protein intake inhibits autophagy. 20 Autophagy is essential to clear cell debris and intracellular bacteria in order to provide metabolic precursors.…”
Section: Protein Intakementioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Presumably, timing of nutrition interventions 18 might play an important role, and especially early (ࣘ3 days) high protein intake may relate to negative effects. 19 Suggestions have been made that early protein intake inhibits autophagy. 20 Autophagy is essential to clear cell debris and intracellular bacteria in order to provide metabolic precursors.…”
Section: Protein Intakementioning
confidence: 99%
“…However, this is not supported by few randomized controlled trials (RCTs) that have been performed in general ICU patients and other evidence from septic patients . Presumably, timing of nutrition interventions might play an important role, and especially early (≤3 days) high protein intake may relate to negative effects . Suggestions have been made that early protein intake inhibits autophagy .…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to these findings, in a post hoc secondary analysis of the EPaNIC trial, a cumulative protein dose, rather than the cumulative glucose dose, early during ICU stay was associated with delayed ICU discharge [41]. Further, a single-centre retrospective cohort study (n = 455) reported a lower protein intake (< 0.8 g/kg/day) before day 3 and high protein intake (> 0.8 g/kg/day) after day 3 was associated with lower 6-month mortality (adjusted HR 0.609; 95% CI 0.480-0.772, p < 0.001) compared to patients with overall high protein intake [42]. Prospective, randomised data is required to inform the most appropriate amount and timing of protein to deliver to critically ill patients.…”
Section: Protein Delivery and Clinical Outcomesmentioning
confidence: 98%
“…Bendavid et al concluded in a retrospective study that administrating protein during the early course of the disease (i.e., the first three days) was associated with better survival [85]. On the other hand, the PROTEINVENT retrospective study concluded that high protein intake during the first three to five days of admission to ICU was associated with increased mortality [86]. Until recently, suppling high levels of protein at such an early phase of the illness was only possible by using parenteral nutrition [87].…”
Section: Improved Protein Intakementioning
confidence: 99%